Assessment of Users’ Satisfaction with Library Resources and Services at the Bestlink College of the Philippines: Towards a Guide: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In any service organization, customer satisfaction is of utmost importance. To ensure this, new services, programs, equipment, and facilities are continuously offered to meet customers' needs. Dizon (2010) suggests that evaluating the library collection can provide reliable data for school management to monitor and maintain the library's collection. This enables management to identify strengths and weaknesses, make necessary enhancements, and better understand how various factors affect the execution of their services. The study encourages school administrators to formulate a feasible library development program to upgrade the quality and suitability of their library collections, facilities, and services, particularly in areas where improvements are needed. At Bestlink College of the Philippines, a survey was conducted to gather students' opinions regarding the library's resources, staff services, information accessibility, and general services. The survey included fifty (50) first to fourth-year students who were purposely selected to participate and guided by a set of formulated questions. The main tool used to gather data was the survey questionnaire, and the data collected were analyzed using weighted means.  The analysis revealed that most respondents either had a high level of satisfaction or were dissatisfied with the services offered by the Bestlink College of the Philippines Library. This study provides insight into the student's opinions of the library, and some suggestions may be implemented to improve its resources and services. The main goal of this study is to evaluate the library resources accessible to the college students of Bestlink College of the Philippines. The study was conducted during the academic year 2021-2022 and is restricted to the BCP students who utilize the library. The survey respondents were college students from various programs proposed by Bestlink College of the Philippines.